7 Runx1 deficiency protects against adverse cardiac remodelling following myocardial infarction. (17th November 2015) - McCarroll, CS; He, W; Foote, KK; Nather, K; Fattah, C; Elliott, EBA; Cochrane, A; Bowman, P; Bell, M; Kubin, T; Braun, T; Nicklin, SA; et al.
Abstract : Background: Post-MI various cellular and extracellular matrix changes occur in the infarct, border zone (BZ) and left ventricular (LV) regions of the heart due to death of cardiomyocytes. In a significant proportion of patients with MI, these changes can lead to adverse cardiac remodelling with subsequent reduced myocardial function resulting in heart failure (HF). The transcription factor Runx1, required for the differentiation of haematopoetic stem cells and normally absent in adult cardiomyoyctes, is switched on in BZ cardiomyocytes. Our objective is to answer the question – is Runx1 merely a marker of cardiomyocyte damage or does it play a significant functional role post-MI? Results: Runx1 is expressed within the BZ and remote LV myocardium in a mouse model of MI and its expression negatively correlates with cardiac function measured by pressure-volume (PV) loop analysis. A tamoxifen inducible, cardiomyocyte specific Runx1 deficient mouse has preserved LV systolic function, lack of LV wall thinning and reduced LV dilation post-MI measured by echocardiography and PV loop analysis. Runx1 deficient mice have maintained LV free wall thickness with no change in infarct size or fibrosis 8 wk post-MI. Runx1 deficient mice are protected against eccentric hypertrophy. Functionally, Runx1 deficient mice have larger Ca 2+ transients, increased SR Ca 2+ content, and increased SERCA function with improved contractility 2 wk post-MI. Runx1 deficient mice show reduced PP1 and levels greater PLB phosphorylation Conclusion: Runx1 is a new target with therapeutic potential to improve cardiomyocyte Ca 2+ handling and contractility post-MI thereby preventing adverse cardiac remodelling and progression to heart failure.